Metodologias ativas e contextualização do processo de ensino aprendizagem de bioquímica - Nicoletti, Angelica Markus (2023)
Biochemistry is a discipline, important for professional performance in several areas. Described by many students as impalpable, difficult to learn, which requires dedication, curiosity and “enjoyment” on the part of both the teacher and the student. In understanding its content, the tools used can have an impact, whether or not stimulating students in the world of knowledge. In this context, we hypothesize that active methodologies, in the form of gamification, can act as tools to awaken students' understanding of biochemistry through strategies that refer to games, motivating them to be active in the construction of knowledge. In view of the above, the general objective of this work was to evaluate the taste and enthusiasm of university students for the subject of biochemistry. We also aim to evaluate the use of active methodologies, as a tool in the construction of knowledge. To this end, questionnaires called pre- and post-test were applied, together with the active methodologies tool in the form of gamification. The target audience were undergraduates from the veterinary, zootechnics and chemistry and biology courses at the Federal University of Santa Maria, RS. As a result, through the application of questionnaires and active methodologies, we observed that in the pre-test the proportion of unmotivated students, in the biochemistry discipline, without mastery of the content, was high. We identified that university students already enter biochemistry studies with concepts formed of “not liking the subject”, of it being a “subject that is rotated and studied several times”. However, after applying the tool and post-test questionnaire, the results generally changed, showing a positive influence of the use of active methodologies on content learning and student satisfaction with biochemistry. This tendency for responses to improve and be more assertive in the post-test continued during the different forms of application of the tool, in the different biochemistry questions carried out, with the classes throughout the research. We also identified that the classes and content of biochemistry, are usually not taught with a focus on students' professional use, and are poorly contextualized for their future professional performance. However, we also investigated that a large proportion of students, despite not understanding biochemistry well, are aware of its importance for their professional performance. Finally, we found that there are countless factors that influence the learning process, understanding, “taste” for the subject and also the structuring of a class. Our results showed that the use of active methodologies is important to improve the quality of classes and learning.